THE EFFECT OF NUTRITIONAL EDUCATION THROUGH POSTER MEDIA AND VIDEO ON THE IMPROVEMENT OF KNOWLEDGE ABOUT ANEMIA IN ADOLESCENT PRINCESS - May Astuti, Nur Azizah; Kurniasari, Ratih (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Nutritional anemia is a major nutritional problem in the world, including in Indonesia, which is caused by iron deficiency. Iron deficiency anemia has infected more than 600 million people worldwide and in developing countries the prevalence reaches 51%. In Indonesia, the prevalence of anemia in adolescent girls is 22.7%. The effects of anemia can cause ongoing stress and complications from fatigue. The influencing factor is the lack of knowledge of young women about anemia. Efforts to increase knowledge of young women on anemia health problems can be done through nutrition education. The purpose of this study was to determine the effect of nutrition education through posters and videos on knowledge of anemia in adolescent girls.Methods: The research design used was quasy experimental with a pre-post test group design, which was carried out in April 2021. The research subjects were young women aged 12-18 years consisting of two groups, namely the poster media group and video media, with a total of 40 respondents. Data analysis used paired sample t-test.Results: Based on the results of the Paired Sample T-Test, it showed that knowledge increased after education, both in the poster and video groups. There were differences in respondents' knowledge of the effect of using nutrition education media through posters (p = 0,021) and videos (p = 0,001).Conclusion: Nutrition education has an effect on knowledge of anemia in adolescent girls, as well as more effective education through video media.